Standardized dirts for testing the efficacy of workplace cleaning products: validation of their workplace relevance - Elsner, Peter; Seyfarth, Florian; Sonsmann, Flora Karla; Strunk, Meike; John, Swen Malte; Diepgen, Thomas L.; Schliemann, Sibylle (Contact dermatitis, 2013)
Background In order to assess the cleaning efficacy of occupational skin cleansers, standardized test dirts mimicking the spectrum of skin soiling at dirty workplaces are necessary. Objectives To validate newly developed standardized test dirts (compliant with the EU Cosmetics Directive) for their occupational relevance. Methods In this single-blinded, monocentric questionnaire-based clinical trial, 87 apprentices of three trades (household management; house painting and varnishing; and metal processing) evaluated the cleanability of six standardized test dirts in relation to their workplace dirts. In addition, they judged the similarity of the test dirts to actual dirts encountered in their working environments. Results Most of the household management participants assessed the hydrophilic model dirt (‘mascara’), the lipophilic model dirt (‘W/O cream’) and a film-forming model dirt (‘disperse paint’) as best resembling the dirts found at their workplaces. Most of the painters and varnishers judged the filmogenic model dirts (‘disperse paint’ and ‘acrylic paint’) as best resembling the dirts found at their workplaces. For the metal workers, the lipophilic and paste-like model dirts were most similar to their workplace dirts. Conclusions The spectrum of standardized test dirts developed represents well the dirts encountered at various workplaces. The test dirts may be useful in the development and in vivo efficacy testing of occupational skin cleansers.
Gesehen am 05.02.2021